The potential of JAKABA (eternal fortune fungus) from rice washing water as a liquid biofertilizer for pre-planting soil of mung bean (Vigna radiata L.) - Azrial, Fahmi (Universitas Muhammadiyah Mataram, 2024)
Mung bean (Vigna radiata L.) is a legume crop with high economic value, containing 20-25% protein and rich in vitamins and minerals. Despite its agronomic advantages, its productivity in Indonesia remains low. The quality of planting media and proper nutrient management significantly affect productivity. The use of inorganic fertilizers can negatively impact soil, necessitating alternatives such as liquid biofertilizers. One potential type of liquid biofertilizer is JAKABA, a fungal culture derived from fermented rice washing water. This study aims to determine the effect of JAKABA as a pre-planting liquid biofertilizer on the growth of mung bean plants. The experiment employed a Completely Randomized Design (CRD) with four treatments: P0 (control), P1 (JAKABA 1:5 water), P2 (JAKABA 1:10), and P3 (JAKABA 1:15 water), each replicated four times. The experimental procedure included JAKABA production, mung bean seeding, and watering for seven days. Measured parameters included plant height, stem diameter, number of leaves, leaf length, and leaf width. Data analysis used One Way ANOVA test, followed by Duncan's test at α=5% significance level if significant differences were found. Results showed that the application of JAKABA as a pre-planting liquid biofertilizer had a significant effect on mung bean growth. Application of JAKABA liquid biofertilizer in pre-planting soil significantly enhanced mung bean vegetative growth. The 1:5 water dilution optimally increased plant height (26.35±0.64 cm), stem diameter (0.22±0.05 cm), and leaf count (0.22±0.05), while the 1:15 dilution maximized leaf dimensions (length: 4.12±0.29 cm; width: 3.02±0.38 cm). To conclude, the use of JAKABA as a pre-planting liquid biofertilizer effectively enhancing the vegetative growth of mung bean plants, with varying effectiveness depending on the concentration and observed growth parameters.